2021
DOI: 10.1128/jb.00703-20
|View full text |Cite
|
Sign up to set email alerts
|

Control of the serine integrase reaction: roles of the coiled-coil and helix E regions in DNA site synapsis and recombination

Abstract: Bacteriophage serine integrases catalyze highly specific recombination reactions between defined DNA segments called att sites. These reactions are reversible depending upon the presence of a second phage-encoded directionality factor. The bipartite C-terminal DNA binding region of integrases includes a recombinase domain (RD) connected to a zinc-binding domain (ZD), which contains a long flexible coiled-coil (CC) motif that extends away from the bound DNA. We directly show that the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…However, we observed that while Int maintained its recombinase activity in vitro in the presence of Adi, there was no obvious aberrant nuclease activity when the purified proteins were combined (Figure S5). Adi also did not inhibit the integration reaction as an RDF would ( 41 , 44 , 45 ), further confirming it is not the RDF. The inability to reconstitute destructive nuclease activity in vitro could be due to a missing factor (e.g.…”
Section: Resultsmentioning
confidence: 66%
“…However, we observed that while Int maintained its recombinase activity in vitro in the presence of Adi, there was no obvious aberrant nuclease activity when the purified proteins were combined (Figure S5). Adi also did not inhibit the integration reaction as an RDF would ( 41 , 44 , 45 ), further confirming it is not the RDF. The inability to reconstitute destructive nuclease activity in vitro could be due to a missing factor (e.g.…”
Section: Resultsmentioning
confidence: 66%
“…However, we observed that while Int maintained its recombinase activity in vitro in the presence of Adi, there was no obvious aberrant nuclease activity when the purified proteins were combined (Figure S5). Adi also did not inhibit the integration reaction as an RDF would (41,44,45), further confirming it is not the RDF. The inability to reconstitute destructive nuclease activity in vitro could be due to a missing factor (e.g., other proteins or cofactors in the nuclease buffer).…”
Section: Phage-encoded Adi Requires the Attp Target Sequence And Cata...mentioning
confidence: 70%
“…Lastly, another way in which Int activity can be modulated is through modification of the protein itself. However, we are not aware of any LSRs that can undergo modification, except during recombination in which the LSR is covalently bound to the 5’ DNA ends through a phosphoseryl linkage (26, 3941). Thus, further study of the mechanism by which Adi exploits Int activity to target PLE2 may reveal more widespread modifications to LSR activity than are currently appreciated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still unclear to what extent natural attP and attB sequences are optimal for LSI activity, [ 39–45 ] and it is likely that phages integrate into non‐optimal attB sites in some organisms. Recent studies have suggested ways through which the att sites of LSIs could be redesigned for improved activities by changing the spacing between DNA sections of the att site recognized by specific integrase domains, [ 41,46,47 ] but the universality of these ideas is yet to be tested across a wide range of LSIs. Also, optimization of reaction buffer might be needed for each LSI.…”
Section: Discussionmentioning
confidence: 99%